2015
DOI: 10.1016/j.hrthm.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise ablation approach versus pulmonary vein isolation in patients with paroxysmal atrial fibrillation: Randomized controlled trial

Abstract: In addition to PVI, stepwise ablation achieving sinus rhythm and nonatrial arrhythmia inducibility has relevantly improved the clinical outcome of the PAF control strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…20,21,30,31 Among these common sites of non-PV triggers, the SVC accounted for 76% (28/37) of cases in our study, which was much higher than the range of 6% to 12% reported previously. 22,24,26 The higher incidence of SVC trigger observed in our study might be related to ethnic differences from previous non-Asian studies or our use of a broad definition of non-PV trigger. Consistent with the former possibility, a high incidence (60%) of SVC trigger was reported in a study on an Asian population.…”
Section: Prevalence Of Non-pv Triggersmentioning
confidence: 50%
See 1 more Smart Citation
“…20,21,30,31 Among these common sites of non-PV triggers, the SVC accounted for 76% (28/37) of cases in our study, which was much higher than the range of 6% to 12% reported previously. 22,24,26 The higher incidence of SVC trigger observed in our study might be related to ethnic differences from previous non-Asian studies or our use of a broad definition of non-PV trigger. Consistent with the former possibility, a high incidence (60%) of SVC trigger was reported in a study on an Asian population.…”
Section: Prevalence Of Non-pv Triggersmentioning
confidence: 50%
“…16,[19][20][21][22][23][24][25][26][27][28] Noninducibility of AF achieved by additional ablation after PVI is associated with lower AF recurrence compared with PVI alone. 23,24,28 However, Leong-Sit 29 et al reported that noninducibility of any atrial tachyarrhythmia is not predictive of clinical recurrence at a 1-year follow-up. In our study, a non-PV AF trigger was a predictor for atrial tachyarrhythmia recurrence; however, the identification of a PV trigger or the achievement of noninducibility was not ( Figure 5).…”
Section: Need For An Additional Procedural End Point Beyond Pvimentioning
confidence: 99%
“…CFAEs were described by K. Nademanee, et al in 2004 and several previous studies showed that substrate modification targeted to CFAEs improved arrhythmia-free rate after catheter ablation procedure [15,18,19] . Conversely, broad ablation of all CFAEs could result in greater tissue destruction during catheter ablation for persistent AF and induce complex ATs after procedure [8,20,21] .STAR AF II trial, a recent randomized trial comparing three approaches to substrate ablation for persistent AF, showed no efficacy of CFAE and left atrial linear ablations [9] .Y.…”
Section: Discussionmentioning
confidence: 99%
“…Routine linear, complex fractionated electrograms, and rotor ablations were reported associated with improved clinical outcomes compared with PVI alone ( 6 , 7 , 9 , 19 ). Faustino et al reported a stepwise ablation strategy that accomplished a 90.7% success rate after 12-month follow-up in PAF patients ( 20 ). However, in a more recent study, elimination of triggers as an end point of ablation in patients with PAF showed a lower recurrence compared with stepwise substrate modifications ( 21 ).…”
Section: Resultsmentioning
confidence: 99%